Novel HSP90 inhibitors, NVP-AUY922 and NVP-BEP800, radiosensitise tumour cells through cell-cycle impairment, increased DNA damage and repair protraction - Stingl, L (Nature Publishing Group, 2010)
BACKGROUND: Heat-shock protein 90 (Hsp90) has a crucial role in both the stabilisation and regulation of various proteins, including those related to radioresistance. Inhibition of Hsp90 may therefore provide a strategy for enhancing the radiosensitivity of tumour cells. This study explores the responses of four tumour cell lines (A549, GaMG, HT 1080 and SNB19) to combined treatment with ionising radiation (IR) and two novel inhibitors of Hsp90, NVP-AUY922 and NVP-BEP800. The techniques used included cell and colony counts, expression of Hsp90, Hsp70, Akt, survivin, cleaved caspase 3, p53, cell-cycle progression and associated proteins. DNA damage was analysed by histone γH2AX and Comet assays. RESULTS: We found that NVP-AUY922 and NVP-BEP800 enhanced radiosensitivity in all tested cell lines. In contrast, only two cell lines (HT 1080 and GaMG) exhibited an increased rate of apoptosis after drug pretreatment, as revealed by western blot. In all tested cell lines, the expression of histone γH2AX, a marker of DNA double-strand breaks, after combined drug-IR treatment was higher and its decay rate was slower than those after each single treatment modality. Drug-IR treatment also resulted in impaired cell-cycle progression, as indicated by S-phase depletion and G2/M arrest. In addition, the cell cycle-associated proteins, Cdk1 and Cdk4, were downregulated after Hsp90 inhibition. INTERPRETATION: These findings show that the novel inhibitors of Hsp90 can radiosensitise tumour cell lines of different entities through destabilisation and depletion of several Hsp90 client proteins, thus causing the depletion of S phase and G2/M arrest, increased DNA damage and repair protraction and, to some extent, apoptosis. The results might have important implications for the radiotherapy of solid tumours.